2013
DOI: 10.2147/opth.s39057
|View full text |Cite
|
Sign up to set email alerts
|

Frontal suspension for congenital ptosis using an expanded polytetrafluoroethylene (Gore-Tex®) sheet: one-year follow-up

Abstract: BackgroundThe frontalis suspension technique is the surgical method of choice in patients with ptosis and a levator function of 4 mm or less. Several types of materials have been used, including Gore-Tex®, which has been used successfully as a frontalis sling material since 1986. Recently, a Gore-Tex sheet (wider than a sling or strip) suspension was reported. This paper reports the results of 27 eyes from 20 patients with congenital ptosis treated using the frontalis suspension technique with the newly develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…Ectropion was seen more in GTS, which is more malleable and more liable for overtraction, leading to more exposure with eversion of the lid. This matches with Nakaucia et al’s 18 findings. Ectropion can be managed after surgery with traction exercises.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ectropion was seen more in GTS, which is more malleable and more liable for overtraction, leading to more exposure with eversion of the lid. This matches with Nakaucia et al’s 18 findings. Ectropion can be managed after surgery with traction exercises.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to other studies, 8 as fascia lata can integrate with tissue and potentiate the frontalis muscle action to elevate the eyelid. 17 Nevertheless, Nakaucia et al 18 found that the GTS has satisfactory functional results as it produces more stable traction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no need for redo surgery in any of these cases in one year follow up period of the study [22]. As well, they had one case of exposure of the Gore-Tex sheet in a 71-year-old man who experienced more bleeding than the other patients, and wound recovery was slow [22].…”
Section: Discussionmentioning
confidence: 89%
“…8,19,20 Cable suture slings, such as Prolene or nylon, are particularly susceptible to recurrence; therefore, they are primarily indicated as temporary treatment to prevent amblyopia in severe ptosis. [20][21][22] Expanded polytetrafluoroethylene (ePTFE) is a synthetic porous fluoropolymer with a low recurrence rate 23,24 and an infection rate between 7% and 45.5%. 20,23 Silicone provides the benefits of easy reversibility and increased elasticity, which decreases the risk of lagophthalmos (►Fig.…”
Section: Frontalis Suspension/slingmentioning
confidence: 99%